Thickness optimization of thin-film tandem organic solar cell - Bangash, K.A. (MDPI AG, 2021)
The polymer solar cells also known as organic solar cells (OSCs) have drawn attention due to their cynosure in industrial manufacturing because of their promising properties such as low weight, highly flexible, and low-cost production. However, low Î· restricts the utilization of OSCs for potential applications such as low-cost energy harvesting devices. In this paper, OSCs structure based on a triple-junction tandem scheme is reported with three different absorber materials to enhance the absorption of photons which in turn improves the Î·, as well as its correlating performance parameters. The investigated structure gives the higher value of Î· = 14.33 with Jsc = 16.87 (mA/m2), Voc = 1.0 (V), and FF = 84.97 by utilizing a stack of three different absorber layers with different band energies. The proposed structure was tested under 1.5 (AM) with 1 sun (W/m2). The impact of the top, middle, and bottom subcellsâ thickness on Î· was analyzed with a terse to find the optimum thickness for three subcells to extract high Î·. The optimized structure was then tested with different electrode combinations, and the highest Î· was recorded with FTO/Ag. Moreover, the effect of upsurge temperature was also demonstrated on the investigated schematic, and it was observed that the upsurge temperature affects the photovoltaic (PV) parameters of the optimized cell and Î· decreases from 14.33 to 11.40 when the temperature of the device rises from 300 to 400 K. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.